1998
DOI: 10.1093/oxfordjournals.molbev.a026024
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and phylogenetic utility of the period gene in Lepidoptera

Abstract: Evolution and phylogenetic utility of the period gene are explored through sequence analysis of a relatively conserved 909-bp fragment in 26 lepidopteran species. Taxa range from tribes to superfamilies, primarily within the putative clade Macrolepidotera plus near outgroups, and include both strongly established and problematic groupings. Their divergence dates probably range from the late Cretaceous through much of the Tertiary. Comparisons within the same set of closely related species show that amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
4

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 42 publications
2
55
0
4
Order By: Relevance
“…The two immunoreactive peptides span slightly different regions of the consensus PER protein, but both include sequences flanking the site of the per s mutation, suggesting that the antibodies react with this well-conserved domain of PER (Reppert et al, 1994;Regier et al, 1998). Their reactivity with D. melanogaster PER was confirmed in immunocytochemical experiments, in which they labeled the usual per-expressing cells in wild-type flies (J.N.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The two immunoreactive peptides span slightly different regions of the consensus PER protein, but both include sequences flanking the site of the per s mutation, suggesting that the antibodies react with this well-conserved domain of PER (Reppert et al, 1994;Regier et al, 1998). Their reactivity with D. melanogaster PER was confirmed in immunocytochemical experiments, in which they labeled the usual per-expressing cells in wild-type flies (J.N.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies of PER expression in other insects have used anti-PER-S, an antiserum against a peptide just downstream of the per s mutation (Siwicki et al, 1988), a region that is well conserved among sequenced insect per homologs (Colot et al, 1988;Thackeray and Kyriacou, 1990;Reppert et al, 1994;Regier et al, 1998). In brains of a silkmoth, A. pernyi , a beetle, Pachymorpha sextaguttata (Frisch et al, 1996), and a cricket, Teleogryllus commodus (Honegger et al, 1991), anti-PER-S labeled the somata and projections of some dorsolateral neurosecretory cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deduced sequence with 323 amino acids was judged to be the region corresponding to PAS domain from its similarity to those of other insect PERIOD PAS domains. When this amino acid sequence was compared with the sequence reported by Regier et al (1998), however, we found that the sequence of Bombyx mori PERIOD reported in the database contained an additional five amino acid residues in this PAS domain. The insertion/deletion of GTQEK pentapeptide was found between the Asn(=N) and Ala(=A) residues in a proline-truncated site PKTANAQSP.…”
Section: Isolation Of a Bombyx Mori Period Cdna Fragmentmentioning
confidence: 88%
“…This 15 bp nucleotide sequence corresponds to the amino acid sequence GTQEK. PAS domain sequences are highly conserved among the various insect PERIOD homologues (Regier et al ., 1998). When we aligned the sequence of PAS domains very carefully, however, the domains were classified into two groups: namely, PAS domains with GTQEK or a related pentapeptide and PAS domains lacking such a fragment (Fig.…”
Section: Introductionmentioning
confidence: 99%